KAJIAN PENGOLAHAN UBI KAYU MENJADI MAKANAN KUDAPAN SEBAGAI UPAYA PENINGKATAN PENDAPATAN EKONOMI MASYARAKAT DESA BAJARONGGI KECAMATAN DOLOK MASIHUL KABUPATEN SERDANG BEDAGAI - Rama Indra (Akademi Pariwisata Darma Agung, 2019)
Cassava is the main carbohydrate resource commodity and has a economic potential for the community living in Desa Bajarongi Kecamatan Dolok Masihul Kabupaten Serdang Bedagai. Besides crops and cassava rice, it is also one of the leading commodities in an area. An assessment was conducted in April 2016 on the people of the village of Bajaronggi, Dolok Masihul Subdistrict, Serdang Bedagai District on the use of cassava for horse food. The purpose of the study is that cassava has a good prospect for processed food and can be developed as an increase in economic income through home-based businesses in the village. Survey and direct observation are the methods used in this study. Where sampling is done by sampling or by group, the data is analyzed using descriptive qualitative analysis. The output of this research shows that most of the harvest of cassava is straightly processed and made cassava starch and mocaf (modified cassava flour). The community is tended to underutilization cassava. As it may recognize nowadays that cassava can be used to make variety of products like snacks, cookies and traditional cakes. The community used cassava for their own need only. The total number for cassava harvest is 272.173 tons, which means that this commodity is reasonable to be developed in different kind of processed food products and increased the financial income of the community in Desa Bajaronggi Kecamatan Dolok Masihul Kabupaten Serdang Bedagai.